Exploration of international relations data : an object-oriented approach - Unseld, Sigrid (IEEE Computer Society Press, 1997)
Describes the development of a prototype system that assists users in exploring domain-specific data. The book concentrates on the role of object-oriented programming in addressing technical problems that evolve around data representation and analyses. Exploration of International Relations Data deals with different data structures across data sets, defines efficient operations for different data, matches data format with the data requirements of analysis techniques, and provides a convenient and easy-to-use interface. It illustrates the potential of an object-oriented approach with the respect to data handling and analysis extensibility. Sigrid Unseld's objective throughout the text is to help facilitate the modification and extension of existing data exploration systems to enable users to build new systems tailored to their needs.